Facile green synthesis of calcium carbonate/folate porous hollow spheres for the targeted pH-responsive release of anticancer drugs. Issue 34 (2nd August 2016) - Guo, Yuming; Jia, Weili; Li, Han; Shi, Weike; Zhang, Jie; Feng, Jing; Yang, Lin
Abstract : Calcium carbonate/folate porous hollow spheres were prepared in a facile manner and used for the targeted delivery and pH-responsive sustained release of anticancer drugs. Abstract : Biocompatible hybrid hollow spheres of calcium carbonate/folate with both mesopores and macropores were synthesized using a facile green approach based on Ostwald ripening. The porous hollow spheres were efficiently loaded with doxorubicin, which they were then able to release in a pH-responsive and sustained manner for the targeted treatment of human cancer cells.